2020
DOI: 10.1101/2020.12.20.20248563
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development and external validation of a logistic regression derived formula based on repeated routine hematological measurements predicting survival of hospitalized Covid-19 patients

Abstract: BackgroundThe Covid-19 pandemic has become a global public health crisis and providing optimal patient care while preventing a collapse of the health care system is a principal objective worldwide.ObjectiveTo develop and validate a prognostic model based on routine hematological parameters to predict uncomplicated disease progression to support the decision for an earlier discharge.DesignDevelopment and refinement of a multivariable logistic regression model with subsequent external validation. The time course… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Different assessment procedures within our study also yield highly variable performance estimates. Some studies suggested logistic regression models for COVID-19 and mortality prediction 39,53 , however, most identified (X)GB or RF as the best model classes 18,20,25,31,38 . We confirm these findings and suggest to use XGB or RF for COVID-19 diagnosis and RF for mortality prediction, as these exhibit the highest performance in our experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different assessment procedures within our study also yield highly variable performance estimates. Some studies suggested logistic regression models for COVID-19 and mortality prediction 39,53 , however, most identified (X)GB or RF as the best model classes 18,20,25,31,38 . We confirm these findings and suggest to use XGB or RF for COVID-19 diagnosis and RF for mortality prediction, as these exhibit the highest performance in our experiments.…”
Section: Discussionmentioning
confidence: 99%
“…We additionally report the predictive ability for mortality risk of the COVID-19 positive samples on the basis of the blood tests only, again with no additional expensive features 3335,38,40,41,53,54 . Compared to previous studies 33,36,37,39 , our mortality models are trained on a large number of COVID-19 positive patients.…”
Section: Introductionmentioning
confidence: 99%
“…Mortality risk scores have been developed, by different means, analyzing clinical data and laboratory parameters derived from blood and sometimes urine samples taken on admission to hospital, mostly under the conditions mentioned above [ 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 ].…”
Section: Mortality Risk Scores In Symptomatic Hospitalized Sars-cov-2...mentioning
confidence: 99%
“…However, little is known of the effect of the risk factors identified on the course of the disease. There is a wide range of various models for diagnosing COVID-19, predicting the prognosis of patients with COVID-19 or being admitted to hospital for COVID-19 [5,6] as well as models to support risk stratification scores [7]. In Germany, the indication of a hospital admission is decided by the outpatient doctor dependent upon age, comorbidities, breathing rate and oxygen saturation [8].…”
Section: Introductionmentioning
confidence: 99%